Negovalna diagnoza - Ščavničar, Ema (Obzornik zdravstvene nege, 1998)
Nursing diagnosis is an integral part of nursing process approach. There are many definitions, which have one common theme: it's a stth status of a client.A nursing diagnostic statement has two or three parts. The article includes section on making of nursing diagnosis and a section on classification.
Keywords: diagnostika; Nursing diagnosis; Nursing process; Nursing records; zdravstvena nega